What is the X-Factor in the German Electricity Industry? - Andreas Kuhlmann (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2006)
A new legislation in the German electricity market requires the implementation of an incentive-based regulation within the next years. In such a regime either prices or revenuesare capped and grow with the inflation rate minus a factor, which accounts for productivitydifferences between the sector and the rest of the economy. This paper derivessuch an X-factor for the German electricity industry using a new productivity databaseand Growth Accounting methodology. Considering that several underlying assumptionsare violated due to market imperfections, the calculated X-factor rises from 0.48 to amodified value of 2.15.
Keywords: D24; G38; L43; L51; 330; Electricity; productivity analysis; price cap regulation